Semiconductors: Crystal Imperfection Modulation Engineering for Functionalization of Wide Band Gap Semiconductor Radiation Detector (Adv. Electron. Mater. 2/2018). (12th February 2018) - Ji, Xu; Chen, Liang; Xu, Mengxuan; Dong, Mei; Yan, Kun; Cheng, Shuang; Kong, Xueqian; Wang, Tongyao; Liu, Jiandang; Gu, Bingchuan; Wang, Huanhua; Liu, Zhiyong; et al.
Abstract : Controllable and repeatable crystal‐imperfection‐modulation engineering (CIME) is important for the development of semiconductor science and technology. A universal and feasible CIME for ZnO based on creative electrochemical doping and strong oxidizing thermodynamic annealing processes is described by Feng Huang, Xiaoping Ouyang, and co‐workers in article number1700307 . Their method could be of major benefit for new wide‐band‐gap semiconductor devices.